2021
DOI: 10.1111/jfpp.15436
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of enrichment in the bioactive components of the functional beverage of Turkish gastronomy by supplementation with purple basil (Ocimum basilicumL.) and the ultrasound treatment

Abstract: Ocimium Basilicum L. known as purple basil (PB) is a member of the Lamiaceae family that has long been used for both seasoning to enhance the flavors of foods and remedies of variety of diseases as complementary and alternative medicine. Previous studies suggested that PB could have potential clinical applications for treating diseases related to cancer, allergy, inflammation, and infections against bacterial, fungal, and viral due to its naturally occurring food compositions rich in polyphenol, aromatic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…At the same time, it was found that 2 aroma compounds (Hexyl acetate and 2-nonanone) disappeared after thermal pasteurization and ultrasound treatment. It was found in similar studies that thermal pasteurization damaged some aroma compounds(Doguer et al, 2021;Yıkmış et al, 2020). As a result, when we compare the two processes, 5 compounds were destroyed by pasteurization and 2 compounds by ultrasound.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…At the same time, it was found that 2 aroma compounds (Hexyl acetate and 2-nonanone) disappeared after thermal pasteurization and ultrasound treatment. It was found in similar studies that thermal pasteurization damaged some aroma compounds(Doguer et al, 2021;Yıkmış et al, 2020). As a result, when we compare the two processes, 5 compounds were destroyed by pasteurization and 2 compounds by ultrasound.…”
mentioning
confidence: 70%
“…Analysis of the volatiles were performed by a solid-phase microextraction (SPME) method described by Doguer et al (2021), using a GC-MS system (Shimadzu Corp.). The identifications were achieved by comparing the mass spectra of unknown compounds with those in Wiley 8 and NIST 05 mass spectral laboratory.…”
Section: Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sonochemical effect produced by ultrasound increases aromatic rings of phenolic compounds via the sonophysical effects of acoustic cavitation. This increases the number of polyphenols and works as antioxidants [84] . The drink loaded with bioactive were analyzed for anticancer activity with the help of CCK-8 assay on human colon carcinoma cells (Caco-2); these cells were treated with different concentrations ranging from 250 −400 μl/ml.…”
Section: Anticancer Benefits Of Usae Bioactives From Various Food Sou...mentioning
confidence: 99%
“…The results showed a 75 % cell reduction in Caco-2 compared to the non-treated groups at the highest concentration of 400 μl/ml. The half-maximal inhibitory concentration (IC 50 ) for ultrasound-treated purple basil drink is 276.6 μl/ml [84] .…”
Section: Anticancer Benefits Of Usae Bioactives From Various Food Sou...mentioning
confidence: 99%